The term “leisure” - “old school” or a forward-looking corrective? Moments of leisure as an interlinked characteristic of pedagogical professional acting. An essay (Pedagogical Horizons, 2021)
The ancient term of leisure is described and commented on in its historical context, guided by literature. References by Aristotle, Seneca, Goethe, Pestalozzi, Rainer Maria Rilke, Martin Wagenschein and Hannah Arendt support the substantive framework for a semantic topicality and current relevance of this term. The discussion about its plausible adaptation for the practical school field leads to a realistic model of the interlinking of work and leisure.
Keywords: Reform as a „reforma”; leisure as a highly sensitive and vigilant activity; pausing and reflecting as opposite poles with a view to mediatization of education